The Fookien Times Philippines Yearbook. (Manila, Philippines : The Fookien Times Yearbook Publishing Co., Inc., 1977)
The 60th anniversary edition of the Philippines Yearbook of the Fookien times presents outstanding articles and reviews of the country's condition on the previous year. It includes special anniversary section, The Philippine yearbook destination and centennial section. It drives historians and researchers to a true picture of the previous years' events in the country.
The presidency -- The first lady -- Religion -- The year and events -- National security -- Foreign affairs -- National economy -- Industry -- Tourism -- Trade -- Banking and stocks -- Infrastructure, transportation and communications.
Includes index.
Keywords: PHILIPPINES; PERIODICALS